Rapid reduction in triglyceride levels by therapeutic plasma exchange in patients with hypertriglyceridemic pancreatitis. Issue 1 (30th November 2021) - Chen, Zhu; Huang, Xiaolong; Zhang, Minwei; Han, Na; Ning, Yaogui
Abstract: Objective: To investigate the effect of therapeutic plasma exchange (TPE) on lowering triglyceride (TG) levels in patients with hypertriglyceridemic pancreatitis (HLAP). Methods: The TG‐lowering in patients with HLAP was compared between the TPE group and conservative treatment group (non‐TPE). The primary outcome was TG reduction to less than 500 mg/dL within 48 hours. Results: The primary outcome was significantly correlated with TPE (univariate analysis odds ratio [OR] 2.74; 95% confidence interval [CI] 1.30‐5.79, P = .008; multivariate analysis OR 3.03; 95% CI 1.28‐7.19, P = .012). At 24 and 48 hours, conservative treatment resulted in a 48.24% and 70.44% reduction in TG, while TPE resulted in a 70.91% and 76.39% reduction in TG, respectively. A more rapid decrease of in TGs in a short period was clearly associated with TPE ( P < .001 for interaction). After 72 hours, the TGs decreased by approximately 77% in both groups, with no significant difference ( P = .563). There was no difference between groups in clinical outcomes over the acute time period or over the longer term. Conclusions: In patients with HLAP, TPE resulted in a short‐term and rapid reduction in plasma TG concentrations, with no significant advantage over non‐TPE after 72 hours.